Hubungan Kualitas Hidup Dan Depresi Pada Pasien dengan Perawatan Hemodialisis di Rumah Sakit Swasta Bandung - Riana Rebecca lasut; Jeanny Rantung (Syntax Corporation Indonesia, 2023)
Hemodialysis is given to patients with acute kidney disease and requiring dialysis therapy, where depression is a psychological reaction that is often experienced and is closely related to the patient's quality of life. This study will observe the relationship between quality of life and depression in patients with hemodialysis treatment. An observational analytic design with a cross-sectional approach was used in this study, which was carried out in April 2023 at a hemodialysis unit belonging to a private hospital in Bandung. Respondents consisted of 50 patients undergoing hemodialysis treatment who met the inclusion criteria. A questionnaire with the Beck Depression Inventory II (BDI II) scale was used to measure depression and WHOQOL-BREF was used to measure quality of life. The results showed that of the 50 patients undergoing hemodialysis therapy, 36 (72%) had normal conditions, nine (18) had mild mood disorders, two (4%) had clinical depression, two (4%) had moderate depression, one (2 %) had severe depression, three (6%) had fair quality of life, nine (18%) showed good quality of life, and 38 (76%) had very good quality of life. Statistical data shows a significant correlation (0.041 < 0.05) between depression and quality of life index. Depression is significantly related to the quality of life of patients undergoing hemodialysis therapy. The relationship between depression and quality of life has a weak correlation strength with a negative correlation direction. It is necessary to provide biopsychosocial and spiritual nursing care regarding the risk of depression and improve the quality of life of patients and dig deeper into depression and the quality of life of patients undergoing hemodialysis by using qualitative research methods and increasing the number of larger samples and research populations.